2014
DOI: 10.2322/tastj.12.pn_9
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Mountainous Landslides by SAR Polarimetry: A Comparative Study Using Pi-SAR-L2 and X-band SARs

Abstract: In this paper, we evaluate the polarimetric sensitivity of multi-frequency synthetic aperture radars (SARs) for detecting landslide areas in forest-covered mountains. We tested L-band airborne and X-band spaceborne SARs, i.e. the airborne Polarimetric Interferometric SAR in L-band (Pi-SAR-L2), Terra SAR X, and Cosmo Skymed, at the Totsukawa-mura test site in Nara, Japan. We found that three parameters-the coherence of HH and VV, polarimetric entropy, and the power ratio of HH/HV-are very effective, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
0
8
0
2
Order By: Relevance
“…Note, however, that the observation geometry has not been taken into consideration in these papers. Additionally, the correlation coefficient between HH (horizontal transmitted and horizontal received) and VV (vertical transmitted and vertical received) polarizations and other polarimetric indices were focused on for landslide detection in Shimada et al [6]. They revealed that the magnitude of the HH-VV correlation coefficient showed high values at landslides and smooth surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Note, however, that the observation geometry has not been taken into consideration in these papers. Additionally, the correlation coefficient between HH (horizontal transmitted and horizontal received) and VV (vertical transmitted and vertical received) polarizations and other polarimetric indices were focused on for landslide detection in Shimada et al [6]. They revealed that the magnitude of the HH-VV correlation coefficient showed high values at landslides and smooth surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the applicability of the methods used in this study might be hindered if both the ascending and descending data pairs are not available. Besides the intensity and coherence, the use of SAR polarimetry, polarimetric decomposition and the synergetic use of optical and polarimetric SAR data are also showed effectiveness in landslide detection [6,[42][43][44]. As each method has advantages and shortcomings when selecting a method for landslide detection purpose, the priority must be given based on the availability of SAR data, geographic conditions of the target area, and the nature of the landslide.…”
Section: Discussionmentioning
confidence: 99%
“…Landslides can also be mapped by the backscattered energy difference using SAR imagery before and after a landslide (Yamada et al, 2013;Konishi and Suga, 2018) or with polarimetry-based approaches (Rodriguez et al, 2002;Czuchlewski et al, 2003;Shimada et al, 2014;Shibayama et al, 2015;Plank et al, 2016). Several polarimetric decomposition methods have been developed for classifying land cover based on scattering mechanisms Pottier, 1996, 1997;Freeman and Durden, 1998).…”
Section: Landslide Mappingmentioning
confidence: 99%